Advanced structural inorganic chemistry - Li, Wai-Kee (Oxford University Press, 2008)
A revised and updated English version of a postgraduate textbook that has grown out of several years of classroom development. The term "inorganic" is used in a broad sense as the book covers the structural chemistry of representative elements (including carbon) in the Periodic Table, organometallics, coordination polymers, host-guest systems and supramolecular assemblies